2004
DOI: 10.1038/nature02506
|View full text |Cite
|
Sign up to set email alerts
|

Interdecadal variation in the extent of South Pacific tropical waters during the Younger Dryas event

Abstract: been described for the present day 26 and the mid-Holocene 27. Coupled Sr/Ca and d 18 O analyses at biannual and monthly resolution on the YD Diploastrea permit us to derive information about the coupled ocean-atmosphere response to YD cooling indicated by changes in the balance of evaporation and precipitation (Figs 2 and 3). When the relative contributions of SST and changes in d 18 O SW to the coral d 18 O record are deconvolved 24,25 , we find that d 18 O SW tracks SST variability. Although the error on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
86
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(93 citation statements)
references
References 29 publications
5
86
2
Order By: Relevance
“…S9). The Sr/Ca ratios in coral skeletons are an established proxy for SST variability 10,11,[25][26][27][28] . Here we present a monthly resolved Sr/Ca-based SST reconstruction for a time window of 22 years generated from our HS1 coral (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S9). The Sr/Ca ratios in coral skeletons are an established proxy for SST variability 10,11,[25][26][27][28] . Here we present a monthly resolved Sr/Ca-based SST reconstruction for a time window of 22 years generated from our HS1 coral (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, seasonally resolved records from fossil shallow-water corals were successfully used to reconstruct interannual ENSO variability in the tropical Pacific during the last glacial 9 , but represent short intervals older than 38,000 years only. A few coral records are available for intervals of the last glacial termination [10][11][12][13][14] , but are too short to document significant interannual ENSO variability. In modern observations, ENSO variability is described by monitoring tropical Pacific sea surface temperature (SST) 15 .…”
mentioning
confidence: 99%
“…This work presented new measurements of Sr/Ca, Mg/Ca and Ba/Ca in the finest temporal resolution to date in the carbonate geochemistry literature [1][2][3][4][5][6][7][8][9] . Although there is some ambiguity in the age model, the giant clam Sr/Ca data clearly demonstrated the daily light cycle, which we attributed to insolation-driven, differential rates of growth and calcification.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, biogenic marine carbonates are important tools for reconstruction of the past climate system. Proxies reflecting past seawater temperature [1][2][3] , salinity 4,5 , pH 6,7 , and nutrients 8,9 has been derived from stable isotopes and trace elements in coral skeletons, foraminifera tests, and mollusk shells. Insolation is an important component of meteorological data, as solar energy is the primal and direct driver of weather and climate.…”
mentioning
confidence: 99%
“…An intriguing feature of our record are large reservoir age increases that just precede growth hiatuses, suggesting a concomitant decrease in water temperature ( Figure 5). We know from trace element studies of this same coral that the average sea surface temperature (SST) at the time was 4.5 °C cooler than today, and that this was accompanied by substantial SST variability (Corrège et al 2004). It is also observed that the coral only recovered from the growth hiatus after the reservoir age dropped to lower values.…”
Section: Location Time Rangementioning
confidence: 85%